IMPLIKASI ETIKA DAN PARADIGMA PEDAGOGIS KEBIJAKAN TRANSFORMASI DIGITAL PENDIDIKAN DI INDONESIA - Marya, Marya Ulfa; Diyan Firmansyah; Ma’rivatul lativah; Tin Amalia Fitri; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The massive digital transformation policy in Indonesia's education sector promises breakthroughs in the quality and accessibility of learning. However, behind the technocratic optimism, there are deep implications that touch aspects of ethics, pedagogy and state respo nsibility. This research aims to critically analyze three fundamental issues: (1) the ethical impact of collecting and using student data on a large scale; (2) fundamental changes in pedagogical paradigms that accompany technology adoption; and (3) the role of the state in navigating the tension between digital innovation and protecting children's rights. Using library research methods on curated journal articles and relevant books, this research found that the practice of collecting student data poses serious risks to privacy and demands a redefinition of the teacher professional code of ethics in the digital era. Furthermore, it was found that the changes that occurred were often still instrumental, rather than a substantive pedagogical paradigm transformation. The state, in its role as a regulator, is faced with the crucial challenge of formulating policies that not only encourage technological progress, but also ensure fairness, inclusiveness and security for students. The implications of this research emphasize the urgency of shifting focus from simply implementing technology towards developing a digital educational ecosystem that is humane, ethical and centered on empowerment.